Unusual presentation of a rectal foreign body: a diagnostic dilemma - Lee, Pei Pei; Chuah, Jitt Aun; Sriram, Ratha Krishnan (International Surgery Journal, 2019)
Rectal foreign bodies present a challenge to surgeons from obtaining the correct diagnosis to managing the patient due to a wide array of presentation. Diagnostic dilemmas often arise as patients are sometimes unwilling to disclose the actual history and seek medical attention late. We present a case of a 65 year old Asian gentleman who present with history of per-rectal bleeding, tenesmus, acute urinary retention, constitutional symptoms with investigations suggestive of rectal malignancy. Intraoperatively identified a rubber-like foreign body tightly packed in the pelvic-cavity with severe injury to the rectum requiring abdominal-perineal resection.